(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article highlights the relevance of synthetic liquid fuel production today. With the increase in the types and movement of land, air, and water transport in the world, fuel consumption is also increasing day by day. To meet the demand for fuel, a number of energy-efficient, environmentally friendly synthetic liquid fuel productions is being launched. In this regard, obtaining synthetic fuel using local raw materials is the most urgent task for chemists, technologists, and engineers who are currently studying synthetic fuel issues. In Uzbekistan GTL technology based on being taken synthetic from our fuels one diesel fuel traditional diesel to fuel relatively one how much advantage in return world to the standards answer is giving. This and the domestic market Our Republic’s fuel demand is met oil and gas in the field the most big achievement is GTL diesel working release beginning Uzbekistan fuel independence strengthens and internal the market high good quality products with provides.